Impact of a vincristine dose cap on the incidence of neuropathies with DA-EPOCH-R for the treatment of aggressive lymphomas. Issue 5 (15th April 2020) - Weis, Taylor M.; Marini, Bernard L.; Nachar, Victoria R.; Brown, Anna M.; Phillips, Tycel J.; Brown, Julia; Wilcox, Ryan A.; Kaminski, Mark S.; Devata, Sumana; Perissinotti, Anthony J.
Abstract: The CALGB/Alliance 50303 trial found a fivefold increase in the rate of severe neuropathies with DA-EPOCH-R compared to R-CHOP. A likely cause is a higher, uncapped dose of vincristine which is unique to DA-EPOCH-R. Due to a potential for increased toxicity and a paucity of literature confirming improved efficacy with higher vincristine doses, our institution implemented a 2 mg vincristine dose cap with DA-EPOCH-R. We conducted a single-center, retrospective cohort study assessing rates of neuropathy in patients receiving DA-EPOCH-R with or without a 2 mg vincristine dose cap. Patients who received a 2 mg vincristine dose cap had a significant reduction in the incidence of grade 2+ neuropathy (40.9% vs. 84.1%, p = .001) and a significantly longer time to onset of grade 2+ neuropathy (not reached vs. 63 days, p = .001). A vincristine dose cap of 2 mg per cycle may reduce the neurotoxicity-associated morbidity of DA-EPOCH-R.